2021
DOI: 10.1039/d1ra06023f
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Keggin heteropolyacid/Ni-MOF catalyst for esterification of fatty acids

Abstract: The developed heteropolyacids immobilized on Ni-MOF catalysts have strong acidity and perform well in esterification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 53 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…Martínez-Edo and team [88] have reported a few studies in which mesoporous silica-derived catalysts were used to produce biodiesel. Under optimal reaction conditions, Zhang et al [89] observed 86.1 % conversion during esterification of oleic acid using HPMo/Ni-MOF catalyst. The catalyst was synthesized using a one-pot solvothermal method and demonstrated good catalytic activity.…”
Section: Metal Organic Framework(mofs)-based Nanocatalystmentioning
confidence: 99%
“…Martínez-Edo and team [88] have reported a few studies in which mesoporous silica-derived catalysts were used to produce biodiesel. Under optimal reaction conditions, Zhang et al [89] observed 86.1 % conversion during esterification of oleic acid using HPMo/Ni-MOF catalyst. The catalyst was synthesized using a one-pot solvothermal method and demonstrated good catalytic activity.…”
Section: Metal Organic Framework(mofs)-based Nanocatalystmentioning
confidence: 99%
“…Traditionally, biodiesel production is carried out using liquid acid/alkali catalysts due to their high catalytic activity. Unfortunately, these homogeneous catalytic processes exhibit numerous disadvantages, such as high operating costs for steps such as product purification, catalyst neutralization, and a large amount of industrial wastewater that requires treatment [ 9 ]. With regard to this, the utilization of heterogeneous catalysts is becoming an efficient candidate for the production of biodiesel, because of their simple recovery, ease of reuse, insolubility in reaction solvents, and reduction in waste treatment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, HPAs have poor affinity for CO, and are hence unsuitable for methanol carbonylation when used in isolation; combination with a CO binding metal, either by ion-exchange of H 3 O + (which bind Keggins into a secondary crystalline structure), lacunary substitution into the primary Keggin unit, [27][28][29] organic modification, 30 or composite formation. 31 Rhodium modified Cs salts of 12-tungstophosphoric acid (HPW) can successfully perform DME carbonylation, but typically exhibit low surface area (100 m 2 g −1 ) and limited opportunity for tuning their porosity. 9,29 We previously reported a silica supported, bifunctional Rh-xantphos-HPW catalyst 28 for MeOH carbonylation which exploited the excellent thermal stability of the xantphos ligated Rh complex 32 and high support surface area and hydroxyl loading to maximise the HPW dispersion and acid site accessibility.…”
Section: Introductionmentioning
confidence: 99%
“…However, HPAs have poor affinity for CO, and are hence unsuitable for methanol carbonylation when used in isolation; combination with a CO binding metal, either by ion-exchange of H 3 O + (which bind Keggins into a secondary crystalline structure), lacunary substitution into the primary Keggin unit, 27–29 organic modification, 30 or composite formation. 31 Rhodium modified Cs salts of 12-tungstophosphoric acid (HPW) can successfully perform DME carbonylation, but typically exhibit low surface area (100 m 2 g −1 ) and limited opportunity for tuning their porosity. 9,29…”
Section: Introductionmentioning
confidence: 99%